An Atypical Presentation of Bartter Syndrome Type 3 With Hypocalciuria and Opisthotonus Posture in a Preterm Infant - Karim Hassan; Imad Afara; Ali Harajli; Jawad Allam; Kaity Saliba; Frederic Harb (Clinical Case Reports)
ABSTRACT This case highlights an unusual presentation of Bartter Syndrome Type 3 marked by hypocalciuria and opisthotonus posture. Recognizing such atypical neuromuscular signs is essential for early diagnosis, genetic confirmation, and targeted management in pediatric patients with electrolyte imbalances.